Rule-based Clinical Decision Support System using the OpenEHR Standard - Silva, Sarah Tifany (2022)
Clinical Decision Support Systems present diverse ramifications that ultimately help healthcare professionals in their decision-making process. These systems can manifest themselves in the form of computerized guidelines that, depending on their goal and stipulated directives, help and optimize healthcare professional’s daily tasks. However, nowadays there is a certain resistance from the healthcare community towards using these systems, with valid justifications such as: the absence of transparency in defined rules, the lack of interoperability within these systems and the difficulty in their usage as they prove themselves unintuitive and hard. With the intention of culminating these flaws, a clinical decision support system was developed based on the openEHR module in order to ensure standardization and semantic interoperability. This system will be oriented towards management and creation of clinical guidelines based on the specifications of the openEHR standard.